Modern pollen and vegetation relationships in Northeastern Patagonia (Golfo San Matías, Río Negro) - Marcos, Maria Alejandra (2012)
The understanding of modern pollen is a critical component of palaeocological research. The pollen assemblages reflect general patterns in vegetation distribution; however, pollen representation is biased by several factors such as differences in pollen production, dispersal and preservation. Therefore, this relationship cannot be applied directly in pollen records of the past. The aim is to study the relationship between modern pollen and vegetation and to apply this new information on the interpretation of Holocene pollen records. Classification of the vegetation into groups corresponding to different geomorphological units was carried out by cluster analysis. Discriminant Analysis was applied on the surface samples to test if different vegetation types could be distinguished by their pollen assemblages. To evaluate the relationship between pollen assemblages and vegetation types, association (A), under-representation (U) and over-representation (O) indexes were calculated for all present taxa in both plant and pollen dataset. The main vegetation types are reflected in pollen assemblages but with greater differences in the proportions of Poaceae, Hyalis argentea, Chenopodiaceae, Asteraceae subf. Asteroideae and Larrea divaricata. Association and representation indexes provided information related to the production rate and pollen dispersal. This study helps to interpret Holocene vegetation and environmental changes from fossil pollen records of the study area.